Takhrij and Syarah Hadith of Chemistry: Air Pollution from Chemical Contents in Motor Vehicle Exhaust Gases - Tara Alvianti; Muhammad Jauhar Kholish; Badri Khaeruman; Casram Casram; Nisa Nur Khasanah (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Saw. about madharat caused by motor vehicle exhaust emissions. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this research is to conduct takhrij to see the authenticity of the hadiths and the implementation of syarah regarding the hadith about madharat in connection with the discussion of chemical content in motor vehicle exhaust gases. The conclusion of this research is takhrij and syarah hadith of the Prophet Saw. about the harm from air pollution caused by motor vehicle exhaust gases which are harmful to living things.